Brugada Syndrome in an Active Duty Air Force Senior Pilot - Walker, Dennis D.; Johnson, Monica L.; Craig-Gray, Robert W.; Loyd, Frank (Military medicine, 2008)
Brugada syndrome describes a subgroup of patients at risk for polymorphic ventricular tachycardia, ventricular fibrillation, and sudden cardiac death and is likely underdiagnosed among aviators. A 40-year-old male pilot presented to the clinic for his physical. He denied any symptoms on initial questioning. Subsequent electrocardiogram (ECG) revealed premature ventricular couplets with ST-segment elevation in V1 and V2 of the precordial leads with T-wave abnormalities. Special care must be taken if ECG demonstrates a Brugada pattern-especially in patients with a history of syncope or a family history of sudden death. Recent studies have confirmed a significant risk reduction in symptomatic patients with type 1 Brugada to as low as 0.8% to 3% with an implantable cardioverter defibrillator. Symptomatic patients displaying type 1 Brugada ECG (spontaneous or after sodium channel blockade) should receive an implantable cardioverter defibrillator and must be permanently disqualified. The Aeromedical Consultation Service should review all cases of Brugada syndrome and render a return to fly for asymptomatic nondiagnostic Brugada types.